STUDY OF THE ROLE OF CENTRAL BANKS IN INDONESIA - Didi Firmansyah; Wiwied Risdianto Putri; Fitri Annisa; Arini Juwita Ayu; Miftahul Jannah; Dewi Mahrani Rangkuty (PT. Arsil Reka Engineering, 2023)
The research aims to find out the history of development and monetary policy of the Central Bank of Indonesia in financial stability. This type of research is descriptive qualitative research with a literature study research method through literature study. The results of this study explain that the Central Bank is an institution that has an important role in the economy of a nation, especially in the fields of monetary, finance and banking. The purpose of the central bank as stated in the Indonesian Law No. 23 Year 1999 Chapter 3 Article 7 is to achieve and maintain rupiah stability. Another role of Bank Indonesia is in terms of channeling money, especially currency or paper and metal where Bank Indonesia has the sole right to distribute currency. Bank Indonesia has three pillars which are its three areas of duties: setting and implementing monetary policy, regulating and maintaining a smooth payment system, and regulating and supervising banking in Indonesia.